Portraying New Economic Growth Strategies Based On The Mamta Cultural Region Through Tourism In The Province Of Papua - Kambuaya, Berth.; Kambu, Arius (Pasundan Social Science Development, 2024)
This type of qualitative research through a phenomenological approach, while the results showed that Nature-Based Ecotourism Development: Tourism development strategies should focus on ecotourism with the principle of environmental conservation to protect existing ecosystems. While in the aspect of Preserving and Strengthening Local Culture: The appropriate strategy is to preserve and promote local culture through festivals, arts, and crafts, and involve the community in these activities. On the aspect of Improving Tourism Infrastructure and Facilities: The development of tourism infrastructure, including roads, transport, and adequate accommodation facilities, should be a priority. Good accessibility to tourist destinations will increase the number of tourist visits. For the Digital Tourism Promotion aspect: Utilise digital platforms for tourism promotion and marketing. In addition, Local Community Involvement: Tourism development that involves local communities in economic activities such as homestays, tour guides, and craft businesses will provide direct economic benefits to them, while encouraging awareness of the importance of protecting the environment and culture. Collaboration and Partnership: Local governments need to establish partnerships with the private sector, local communities, as well as national and international institutions to support inclusive, sustainable, and local potential-based tourism development.